(untitled) - Le, Chap T. (Hoboken, N.J., 2003)
Provides many real-data sets in various fields in the form of examples at at the end of all twelve chapters in the form of exercises. Covers all of the nuts and bolts of biostatistics in a user-friendly style that motivates readers. Contains notes on computations at the end of most chapters, covering the use of Excel, SAS, and others.
Keywords: Biometry,Medical sciences,Sinh trắc học,Khoa học y khoa; Statistical methods,Phương pháp thống kê